WAYS TO IMPROVE TAXATION OF PROPERTY INCOME OF NATURAL PERSONS (Web of Technology: Multidimensional Research Journal, 2024)
In the thesis, the reforms implemented in the development of business activity, natural persons engaged in business activity and the mechanisms of their taxation were studied, suggestions were made regarding the further improvement of the current procedure of property income taxation and the introduction of new mechanisms for increasing the property income of individuals.